2013
DOI: 10.1109/jstars.2012.2227245
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Linear Regression-Based Noise Estimation for Hyperspectral Imagery

Abstract: Abstract-In the traditional signal model, signal is assumed to be deterministic, and noise is assumed to be random, additive and uncorrelated to the signal component. A hyperspectral image has high spatial and spectral correlation, and a pixel can be well predicted using its spatial and/or spectral neighbors; any prediction error can be considered from noise. Using this concept, several algorithms have been developed for noise estimation for hyperspectral images. However, these algorithms have not been rigorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 29 publications
0
53
0
Order By: Relevance
“…Therefore, we can incorporate the high correlations between bands for noise estimation, such as SSDC, which is a useful method for hyperspectral image noise estimation. In SSDC, the spatial and spectral correlations are removed through a multiple linear regression model, and the remaining residuals are the estimates of noise [49,50,58]. Recent works show that SSDC can offer reliable results for noise estimation when there are different land cover types in the hyperspectral images [50].…”
Section: Proposed Okmnf Methodsmentioning
confidence: 99%
“…Therefore, we can incorporate the high correlations between bands for noise estimation, such as SSDC, which is a useful method for hyperspectral image noise estimation. In SSDC, the spatial and spectral correlations are removed through a multiple linear regression model, and the remaining residuals are the estimates of noise [49,50,58]. Recent works show that SSDC can offer reliable results for noise estimation when there are different land cover types in the hyperspectral images [50].…”
Section: Proposed Okmnf Methodsmentioning
confidence: 99%
“…As can be clearly seen from Figure 1, the noise level of the five representative bands is different, and the noise levels of bands 1 and 220 are obviously higher than those of the other three bands. Besides, the previous works correlated with noise estimation of HSI [52][53][54] have demonstrated that the hyperspectral imaging spectrometers adopt very narrow band, which makes the energy acquired in each band not enough to obtain high signal-to-noise ratio (SNR), and the HSI is usually corrupted by wavelength-dependent and sensor-specific noise, which not only degrades the visual quality of the HSI but also limits the precision of the subsequent image interpretation and analysis. That is to say, the noise of HSI is wavelength-dependent, thus the noise levels of different bands are different.…”
Section: The Proposed Su-nlementioning
confidence: 99%
“…To overcome the above mentioned problem, according to the Figure 1 and the previous works correlated with noise estimation of HSI [52][53][54], it is natural to assume that the noise levels at different bands are different. We adopt a simple and efficient noise estimation method based on the multiple regression theory, developed by Bioucas and Nascimento [52], to estimate the noise in each band of HSI.…”
Section: The Proposed Su-nlementioning
confidence: 99%
“…Although those selected bands with sparsity have strength to the small-sample-size problem, the random noise due to the very narrow bandwidth of the hyperspectral sensor negatively affects to the prediction model. One simple noise estimation algorithm uses the mean of standard deviations of several visually homogeneous regions as noise estimate (Gao et al, 2013). However, the homogeneous areas within an image need to be manually selected in this method.…”
Section: Fused Lasso Regression For Noise and Peak Shiftmentioning
confidence: 99%
“…Therefore, the prediction models often result in the poor generalization capability (Pappu, 2014). Considering sensor mechanism and practical measurement, energy acquired in each band is not enough to generate high signal-to-noise ratio (S/N) due to the very narrow band interval of typical hyperspectral imaging spectrometers (Gao et al, 2013). The noise in the hyperspectral data can be categorized in two types: periodic noise and random noise.…”
Section: Introductionmentioning
confidence: 99%